Griffin on human rights - Crisp, Roger 1961- (Oxford University Press, 2014)
This volume presents responses to the work of James Griffin, one of the most significant contributors to the contemporary debate over human rights. Leading moral and political philosophers engage with Griffin's views - according to which human rights are best understood as protections of our agency and personhood - and Griffin offers his own reply